Enrofloxacin Pharmacokinetics and Sampling Techniques in California Sea Hares (Aplysia californica) - Mason, Sharon E (J Am Assoc Lab Anim Sci, 2019)
This pharmacokinetic study was designed to determine the pharmacokinetics of enrofloxacin at 5 mg/kg when given to sea hares in their hemolymph. Enrofloxacin is a commonly used antimicrobial in veterinary medicine and potentially could be used to treat sea hares exposed to susceptible bacterial species. We individually identified 8 juvenile Aplysia californica and group housed them in an open seawater flow system at 14 to 18 °C; 2 served as untreated controls. The remaining 6 animals were injected into the hemocoel with 0.030 mL of 22.7 mg/mL enrofloxacin (average dose, 5 to 6 mg/kg). At each time point, 300 µL hemolymph was collected from the pedal hemolymph sinus and HPLC-analyzed for enrofloxacin and ciprofloxacin levels. Enrofloxacin was detected in all dosed animals, at an average peak concentration of 3 µg/mL in hemolymph, and remained in the body for 20.3 h with an average clearance of 0.19 μg×h/mL. No ciprofloxacin was detected in any Aplysia in this study. Hemocoel injection appears to be an effective way to administer enrofloxacin to Aplysia and reach clinically relevant concentrations. Enrofloxacin reached therapeutic target concentrations in A. californica when dosed according to the regimen described in the current report.